Kesiapan Pemerintah Kota Tanjungpinang dalam Mewujudkan Smart City - Mandala, Edward; Ilham, Iip; Rosalia, Dita; Rasid, Dede (Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
The city government so far has carried out its duties and functions properly, based on the functions of planning, implementation and supervision but on the budget side there are still limitations and on the organizational side that has not gone well due to limited human resources which affect performance in implementing the Smart City implementation process. The purpose of this study is to determine the readiness of the Tanjungpinang city government in realizing a Smart City. The type of research conducted by researchers is descriptive qualitative research. The sampling technique used is purposive sampling. In this study, data were collected by means of interviews, observation, and documentation. Data analysis was carried out using qualitative analysis techniques. The results of the research show that in the field of technology, the government has developed infrastructure and public services, in the field of human resources, namely the lack of human resources in the ICT field so that the application of technology is not optimal, and in the institutional field, the direction of the central government to the Tanjungpinang city government is clearly structured. The conclusion of this study is that the city government carries out its duties and functions properly, based on the planning, implementation and supervision functions that have been running quite well even though on the budget side there are still limitations and on the organizing side that has not gone well due to limited human resources which affect performance in implementing Smart City implementation process.